2006
DOI: 10.1038/sj.eye.6702251
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of spatial–contrast function and short-wavelength sensitivity deficits in patients with migraine

Abstract: Aims To study spatial-contrast function and short-wavelength sensitivity deficits in a migraine population with a disease duration of 30 years or less. Materials and methods In this prospective, cross-sectional study, we evaluated 28 subjects with migraine headache and 15 nonheadache healthy controls. Visual fields were evaluated using the Humphrey Field Analyzer 750i and the 30-2, blue and yellow threshold programme. Contrast sensitivity (CS) was measured at 1.5, 3, 6, 12, and 18 cpd spatial frequencies, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 20 publications
3
33
2
1
Order By: Relevance
“…In contrast, a recent study by Yenice et al. (15) found contrast sensitivity reductions in people with migraine across the entire range of spatial frequencies tested (1.5–18 c/deg).…”
Section: Introductionmentioning
confidence: 71%
“…In contrast, a recent study by Yenice et al. (15) found contrast sensitivity reductions in people with migraine across the entire range of spatial frequencies tested (1.5–18 c/deg).…”
Section: Introductionmentioning
confidence: 71%
“…Visual dysfunction may also impair coordination and probably impacts balance in migraine 44 . Spatiotemporal function and motion processing are reportedly abnormal in migraineurs interictally 45,46 and visual fields and contrast functions differ from controls 47 …”
Section: Cerebellar Disorders In Common Mwa and Mwoa Forms Of Migrainementioning
confidence: 99%
“…It has been well documented that the spatial and temporal types of CS decrease in people with glaucoma (11,32,33) . Grating CS tests are promising for the detection of early glaucoma and its progression (32,34) .…”
Section: Discussionmentioning
confidence: 99%
“…Snellen acuity tests have a limited ability to detect fine changes in contrast because high contrast letters (black on white) are used (9) . Also, recent advances in knowledge about refractive surgery, optical tissues, and glaucoma and macular diseases revealed that the Snellen acuity test is inadequate for early detection of eye diseases and measurement of functional vision (6,(10)(11)(12) . CS decreases in all stages of glaucoma and age-related macular degeneration (AMD) have been documented using different testing methods (7,(12)(13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%